2-(1H-Benzotriazol-1-yl)-1-(3-methylbenzoyl)ethyl benzoate - Zeng, Wu-Lan (International Union of Crystallography, 2009)
In the title molecule, C(23)H(19)N(3)O(3), the dihedral angles between the mean plane of the benzotriazole ring system and the benzene and phenyl rings are 9.67 (9) and 86.08 (10)°, respectively. The dihedral angle between the benzene and phenyl rings is 85.89 (11)°. In the crystal structure, weak intermolecular C—H⋯O hydrogen bonds link molecules into chains along [010].